USING PHET-BASED GRAPHING QUADRATICS SIMULATION TO ENHANCE STUDENTS' MATHEMATICAL VISUAL SKILLS - Ahmad Rifai Siregar; Nur Halimah Matondang, Hamidah Nasution (Adisam Publisher, 2025)
This study aims to analyze the effect of using PhET-based Graphing Quadratics simulations on students' mathematical visual skills in graphing quadratic equations. Involving 50 tenth- grade students divided into two groups, with 25 students in the experimental group and 25 in the control group, this research employed a pretest-posttest method to measure students' skill improvement. The results indicate that the experimental group experienced an average posttest score increase of 23.2 points, while the control group only improved by 7.4 points. Statistical analysis using independent t-tests yielded a p-value of 0.001, indicating a significant difference between the two groups. Students in the experimental group also demonstrated a better understanding of key graph elements, such as vertex and axis of symmetry. Student feedback highlighted an increase in interest and motivation when using the simulation, enriching their learning experience. This study recommends the use of PhET simulations as a teaching aid in mathematics education to enhance students' understanding and skills